Hydro and osmopriming effects on some seed germination and seedling vigour characteristics of three wheat (Triticum aestivumL.) lines - رضا رضایی سوخت آبندانی; مهدی رمضانی; منظر محمدی (علوم و فناوری بذر ایران)
To study effects of priming of wheat seeds, three lines was chosen and their germination charachteristics were tested in year 2010 in the laboratory of Qaemshahr unit of Azad Islamic university in the format of factorial based on randomized block design in four replicates . Treatments included three wheat lines )Darya, N 81-18and Nai60 and seven prime solutions )Potassium Nitrate 1 and 2%, Polyethylene glycol )PEG( 5 and 10%, Potassium chloride 2 and 4% and water( and control )without prime(. Although, non of measured characteristics showed significant differences, line 60 obtained maximum germination speed and Darya obtained maximum root length and stem height . Maximum germination rate resulted from priming with 1% Potassium nitrate , hydro-priming and control , and maximum root length and average germination resulted from priming with 2% Potassium nitrate,water and control )no-prime(. Maximum stem length resulted from priming with 2% Potassium nitrate and minimum root and stem length resulted from priming with 1% Potassium nitrate. line N81-18 obtained maximum germination rate and average germination when primed with water , and Dbearya obtained maximum ratio of root weight to stem weight and minimum root length by priming by 2% Potassium nitrate . Darya obtained maximum germination time when primed by 2% Potassium nitrate and 2% Potassium choloride solutions .